2010
DOI: 10.20533/licej.2040.2589.2010.0030
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Problems with Cohesion and Coherence in EFL Essay Writing in Egypt: Different Perspectives

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 32 publications
(26 reference statements)
9
96
0
4
Order By: Relevance
“…The rest of the sentences are not only personalized, but also transferred from the style of Arabic. These samples of topic as well as concluding sentences are in keeping of previous ones that had been mentioned by Ahmed (2010) and Dweik (as cited in Alsamadani, 2010) that Arab writers in English often write around the topic and repeat phrases before stating the main points.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The rest of the sentences are not only personalized, but also transferred from the style of Arabic. These samples of topic as well as concluding sentences are in keeping of previous ones that had been mentioned by Ahmed (2010) and Dweik (as cited in Alsamadani, 2010) that Arab writers in English often write around the topic and repeat phrases before stating the main points.…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings regarding the writing of Jordanian college students in terms of organization of ideas were reported by Lakkis and Abdel Malak (2002). In addition, Ahmed (2010) examined the writing of EFL Egyptian students and reported similar problems in terms of sequencing ideas and writing topic sentences.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They often repeated their ideas, reported few if any valid points, made serious mistakes in grammar and punctuation, and included irrelevant information. Similarly, Ahmed (2010) investigated cohesion and coherence problems in EFL essay writing in the Egyptian context. He reported that the students faced difficulties writing thesis statements, topic sentences, transitioning of ideas, and the sequencing of ideas.…”
Section: The Challenging Nature Of Efl Writing For Arab Studentsmentioning
confidence: 99%
“…Speaking is a way to exchange feelings, emotions, and demands. It is not only a matter of putting utterances together, but it is also an issue of being one of the most significant aspects that is very confusing to master in the learning process (Ahmed, 2010). Chakraverty and Gautum (2000) state that speaking skill is used to convey meaning of spoken words through a set of signs and symbols between a speaker and a hearer.…”
Section: Review Of Literaturementioning
confidence: 99%